A realization of the inverted pendulum and cart - Gonçalves, Júlio (2015)
This paper presents the design and implementation of an inverted pendulum and cart. The platform was built by two students under a one semester curricular unit targeted on the design of electronic systems. The developed mechanical parts of the system were designed using CAD software. A PID control algorithm was implemented. Some experimental tests were performed and the corresponding results are presented.